Current sources of carbon tetrachloride (CCl4) in our atmosphere. (25th January 2018) - Sherry, David; McCulloch, Archie; Liang, Qing; Reimann, Stefan; Newman, Paul A
Abstract: Carbon tetrachloride (CCl4 or CTC) is an ozone-depleting substance whose emissive uses are controlled and practically banned by the Montreal Protocol (MP). Nevertheless, previous work estimated ongoing emissions of 35 Gg year −1 of CCl4 into the atmosphere from observation-based methods, in stark contrast to emissions estimates of 3 (0–8) Gg year −1 from reported numbers to UNEP under the MP. Here we combine information on sources from industrial production processes and legacy emissions from contaminated sites to provide an updated bottom-up estimate on current CTC global emissions of 15–25 Gg year −1 . We now propose 13 Gg year −1 of global emissions from unreported non-feedstock emissions from chloromethane and perchloroethylene plants as the most significant CCl4 source. Additionally, 2 Gg year −1 are estimated as fugitive emissions from the usage of CTC as feedstock and possibly up to 10 Gg year −1 from legacy emissions and chlor-alkali plants.